2011
DOI: 10.1080/15374416.2011.563468
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Eating Scale for Children and Adolescents: Psychometric Characteristics in a Spanish Sample

Abstract: The main objective of this study was to validate the Emotional Eating Scale version for children (EES-C) in a Spanish population and study the differences in emotional eating among children with binge eating (BE) overeating (OE), and no episodes of disordered eating (NED). The questionnaire was administered to 199 children between the ages of 9 and 16 years, from primary and secondary schools.Confirmatory Factor Analysis revealed five scales: eating in response to anger, anxiety, restlessness, helplessness and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 21 publications
0
11
0
4
Order By: Relevance
“…This group includes cognitive [ 3 , 4 ], familial [ 5 ], social [ 6 , 7 ] and affective [ 8 , 9 ] variables. The source literature argues that the majority of studies and publications relates to the relationship between emotional experiences and eating [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…This group includes cognitive [ 3 , 4 ], familial [ 5 ], social [ 6 , 7 ] and affective [ 8 , 9 ] variables. The source literature argues that the majority of studies and publications relates to the relationship between emotional experiences and eating [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…State-Trait Anxiety Inventory for Children (STAIC) is a selfreported anxiety instrument that measures trait (baseline) and state (situational) anxiety. Several studies (5,6) used this instrument to assess self-reported anxiety as it can be considered the definitive method of anxiety measurement related to different situations or episodes in lifetime.…”
Section: Introductionmentioning
confidence: 99%
“…Walfish and Brown (2009) found that bariatric patients endorsed eating more frequently when bored than when experiencing other negative emotions and suggested that interventions aimed at overcoming boredom may be critical to post-surgical success. Others have since conducted psychometric studies on questionnaires to which items related to eating when bored were added (Koball et al, 2012; Perpiñá et al, 2011). In both cases, eating in response to boredom was endorsed with enough frequency to warrant further investigation.…”
mentioning
confidence: 99%